Using heart rate as a physical activity metric. Issue 3 (2nd June 2019) - Eckard, Matthew L.; Kuwabara, Hana C.; Van Camp, Carole M.
Abstract : Physical activity (PA) is critical for a healthy lifestyle. The current study assessed heart rate (HR) as a primary measure of moderate and vigorous PA with four typically developing children. First, individualized HR assessments were conducted to determine moderate and vigorous HR zones. Next, participants engaged in various exercises at a local YMCA facility (i.e., biking, elliptical, basketball, and exergame boxing) to determine how HR during these activities aligned with their individualized HR zones. During exercise bouts, HR was typically above moderate, but below vigorous HR zones for all participants. Additionally, exercises that restricted range of motion (i.e., biking and elliptical) engendered generally lower HR than exercises with greater range of motion. Vocal instructions to exercise at vigorous levels were effective at increasing HR to vigorous levels for one participant. The advantages of using HR as a metric of PA during assessment and intervention are discussed.